Biomass accumulation, plant biometrics and fruit production of watermelon according to changes in source/drain relations - Lins, Hamurábi Anízio; Albuquerque, José Ricardo Tavares de; Queiroga, Roberto Cleiton Fernandes de; Sá, Francisco Vanies da Silva; Pereira, Auderlan de Macena; Silva, Ariano Barreto da; Paiva, Emanoela Pereira de (Comunicata Scientiae, 2016)
The objective of this study was to evaluate the accumulation of biomass, plant biometrics and production of watermelon fruit submitted to changes in source and drain relations. The experiment was conducted in the experimental area of the CCTA/UFCG, PB, Brazil, during the period from September to December, 2013. Seed of the cultivar “Crimson Sweet” were used and the treatments were allocated in 2x4 split plots, with four replications. Plots consisted of plants grown with different number of fruits (1 and 2) and the subplots with dominant stem pruning in different growing seasons (25, 30, 35 and 40 days after transplanting - DAT). Growth characteristics were evaluated. The modifications induced in watermelons by dominant stem pruning and fruit thinning provided changes in photoassimilate partitions and plant production. The modifications induced in watermelons by dominant stem pruning and fruit thinning provided changes in biomass accumulation , biometrics and the watermelon production of fruits. The thinning of plant’s drain (fruit) resulted in more dry mass accumulation of leaves when comparing to fruit, providing a higher total dry mass. Plants grown with two fruits presented the highest harvest index and the highest production, with reduced fruit size. The stem pruning of seedlings at 40 days after transplanting promoted a higher growth and production of watermelon fruits.